Teachers’ and Students’ Perceptions Towards the Station Rotation Model: A Case of Libyan EFL Writing Classroom - Belazi, Najah Abduallah; Ganapathy, Malini (AJELP: Asian Journal of English Language and Pedagogy, 2023)
As information and communication technologies (ICT) have rapidly developed, computers and internet are widely used in many fields. The aftermath of the Covid-19 pandemic has resulted in online and blended education receiving a lot of attention due to the significant increase in online course enrollments. In this vein, this paper will give insights on the teachers and students’ perceptions towards using a model of Blended Learning named the Station Rotation Model (SRM) in a Libyan EFL writing classroom. Using a single case method, two teachers and students using the SRM in a school located in Libya were cross-examined using in-depth interview and focus group discussions. The findings revealed that after the implementation of the SRM model in the Libyan school, both students and teachers were satisfied with the learning outcomes. The findings further pointed out that the SRM resulted into positive educational effects. However, some serious concerns were shown by both teachers and students that need to be addressed. These include factors related to student-teacher motivation, timing issues, teachers and students training to use SRM and related technology. The study recommends that continuous professional and technological development is required for increasing the use of SRM as tool of blended learning in Libyan schools.